2019
DOI: 10.1002/14651858.cd012806.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound, CT, MRI, or PET-CT for staging and re-staging of adults with cutaneous melanoma

Abstract: Ultrasound, CT, MRI, or PET-CT for staging and re-staging of adults with cutaneous melanoma (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 403 publications
0
59
0
5
Order By: Relevance
“…Despite this, upstaging and a change in the pre-scan management plan in 16% of patients imply a meaningful impact. The importance of changes in disease management has been affirmed in the recently published Cochrane review on staging imaging in melanoma [ 10 ]. In the present study, MRI of the brain never revealed a metastasis at baseline and its usefulness in this setting therefore appears dubious.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, upstaging and a change in the pre-scan management plan in 16% of patients imply a meaningful impact. The importance of changes in disease management has been affirmed in the recently published Cochrane review on staging imaging in melanoma [ 10 ]. In the present study, MRI of the brain never revealed a metastasis at baseline and its usefulness in this setting therefore appears dubious.…”
Section: Discussionmentioning
confidence: 99%
“… Tanshinone I and simvastatin significantly inhibit proliferation and PARP1 expression in melanoma A-375 cells. (A) Western blotting was used to determine the effects of mefloquine ( 1 ), simvastatin ( 2 ), dihydroartemisinin ( 3 ), tanshinone I ( 4 ), cryptotanshinone ( 5 ), gossypol ( 6 ) and dioscin ( 7 ) on PARP1 expression in melanoma A-375 cells. Although no statistical difference were found, a inhibition tendency on PARP1 expression for simvastatin and thanshinone I could be seen in the band.…”
Section: Figurementioning
confidence: 99%
“…Melanoma is a heterogeneous disease and one of the most aggressive forms of skin tumour with poor prognosis (7). Melanoma is associated with numerous genetic mutations or alterations in signalling pathways (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma is an aggressive malignant tumor derived from melanocytes, and its incidence is increasing worldwide [ 1 , 2 ]. Melanoma accounts for a small percentage of skin cancers, but accounts for the majority of deaths from such cancers [ 3 ]. Although melanoma can occur all over the body, it occurs most frequently on the skin.…”
Section: Introductionmentioning
confidence: 99%